Achieving Spread, Scale Up and Sustainability of Video Consulting Services During the COVID-19 Pandemic? Findings From a Comparative Case Study of Policy Implementation in England, Wales, Scotland and Northern Ireland - Shaw, Sara E.; Hughes, Gemma; Wherton, Joseph; Moore, Lucy; Rosen, Rebecca; Papoutsi, Chrysanthi; Rushforth, Alex; Morris, Joanne; Wood, Gary W.; Faulkner, Stuart; Greenhalgh, Trisha (Frontiers in Digital Health, 2021)
Requirements for physical distancing as a result of COVID-19 and the need to reduce the risk of infection prompted policy supporting rapid roll out of video consulting across the four nations of the UK—England, Northern Ireland, Scotland and Wales. Drawing on three studies of the accelerated implementation and uptake of video consulting across the four nations, we present a comparative and interpretive policy analysis of the spread and scale-up of video consulting during the pandemic. Data include interviews with 59 national level stakeholders, 55 health and social care staff and 30 patients, 20 national documents, responses to a UK-wide survey of NHS staff and analysis of routine activity data. Sampling ensured variations in geography, clinical context and adoption progress across the combined dataset. Comparative analysis was guided by theory on policy implementation and crisis management. The pandemic provided a “burning platform” prompting UK-wide policy supporting the use of video consulting in health care as a critical means of managing the risk of infection and a standard mode of provision. This policy push facilitated interest in video consulting across the UK. There was, however, marked variation in how this was put into practice across the four nations. Pre-existing infrastructure, policies and incentives for video consulting in Scotland, combined with a collaborative system-level approach, a program dedicated to developing video-based services and resourcing and supporting staff to deliver them enabled widespread buy-in and rapid spread. In England, Wales and Northern Ireland, pre-existing support for digital health (e.g., hardware, incentives) and virtual care, combined with reduced regulation and “light touch” procurement managed to override some (but by no means all) cultural barriers and professional resistance to implementing digital change. In Northern Ireland and Wales, limited infrastructure muted spread. In all three countries, significant effort at system level to develop, review and run video consulting programs enabled a substantial number of providers to change their practice, albeit variably across settings. Across all four nations ongoing uncertainty, potential restructuring and tightening of regulations, along with difficulties inherent in addressing inequalities in digital access, raise questions about the longer-term sustainability of changes to-date.